Bidding for Incompete Contracts - Patrick Bajari; Stephanie Houghton; Steven Tadelis (Fondazione Eni Enrico Mattei (FEEM), 2004)
When procurement contracts are incomplete, they are frequently changed after the contract is awarded to the lowest bidder. This results in a final cost that differs from the initial price, and may involve significant transaction costs due to renegotiation. We propose a stylized model of bidding for incomplete contracts and apply it to data from highway repair contracts. We estimate the magnitude of transaction costs and their impact using both reduced form and fully structural models. Our results suggest that transactions costs are a significant and important determinant of observed bids, and that bidders strategically respond to contractual incompleteness. Our findings point at disadvantages of the traditional bidding process that are a consequence of transaction costs from contract adaptations.
Keywords: D23; D82; H57; L14; L22; L74; 330; Procurement; Construction; Auktionstheorie; Unvollständiger Vertrag; Beschaffung; Schätzung; Straßenbau; Kalifornien